Impunity in Post-authoritarian Brazil: The Supreme Court’s Recent Verdict on the Amnesty Law - Schneider, Nina (European Review of Latin American and Caribbean Studies, 2011)
While numerous countries in post-authoritarian South America have annulled Amnesty Laws issued under authoritarian rule and punished officials involved in repressive organs, Brazil continues to favour impunity. This attitude has recently been confirmed by the Brazilian Supreme Court’s decision to maintain the 1979 Amnesty Law granting de-facto impunity to violators of human rights during the military regime. The article considers this verdict within its historical context, and raises two questions which have previously attracted little attention: First, why has postauthoritarian Brazil processed the experience of the military regime so differently from its neighbouring countries, and what role did the Amnesty Law play in that difference? Second, what does this disinterest in punishment mean? This article concludes that one promising theory highlighted by political scientists – the low degree of participation in civil society in Brazil – cannot fully explain why the vast majority of Brazilians are not interested in punishment, as numerous citizens mobilized during the amnesty movement. It seems to imply that the heterogeneous antiauthoritarian alliance vanished once the Amnesty Law had been achieved. Another key finding is that the disinterest in punishment cannot be interpreted as moral support for the military regime or a sanctioning of its human rights violations, as the amnesty debate in Brazil is more complex. Resumen: Impunidad en el Brasil post-autoritario: fallo de la Corte Suprema sobre la ley de amnistíaMientras numerosos países sudamericanos han derogado las leyes de amnistía, aprobadas por pasados regímenes militares, y castigado a los oficiales de los órganos represivos, Brasil continúa favoreciendo la impunidad. Esta actitud ha sido recientemente ratificada por la Corte Suprema de Brasil, que ha mantenido la ley de amnistía de 1979, garantizando impunidad a los violadores de los derechos humanos durante el régimen militar. El presente artículo analiza este fallo en su contexto histórico, y plantea dos cuestiones a las que se ha prestado poca atención: primera, ¿por qué el Brasil post-autoritario ha tratado su pasado militar de forma tan diferente a sus países vecinos y qué papel ha jugado la ley de amnistía en dicha diferencia? Segunda, ¿qué significa este desinterés en el castigo? Este artículo concluye que una prometedora teoría señalada por politólogos, sobre la debilidad de la sociedad civil brasileña, no explica completamente por qué tantos brasileños no están interesados en el castigo puesto que el movimiento en pro de la amnistía movilizó a numerosos ciudadanos. Pareciera que la heterogénea alianza anti-autoritaria se desvaneció una vez aprobada la ley de amnistía. Otra conclusión importante es que el desinterés en la justicia no puede interpretarse como un apoyo moral al régimen militar o como una justificación a sus violaciones de los derechos humanos, puesto que el debate sobre la amnistía en Brasil es muy complejo.